Automatic control - Djaferis, Theodore E. (Brooks/Cole Pub, 2000)
Uses the concept of automatic control as a unifying idea to explain the field of engineering - and the kinds of problems engineers solve - to first-year students. This book focuses on the basic principle of feedback and shows how it is used to design automatic controllers